Faktor-Faktor yang Berhubungan dengan Perawatan Diri pada Pasien Peningkatan Asam Urat - Heppy Salsabella; Ahmad Ikhlasul Amal; Dwi Retno S (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study was motivated by problems often experienced by gout sufferers, such as severe pain in the joints that recurs, especially at night and in the morning, accompanied by aching, swelling, and redness, with the aim of identifying factors related to self-care in patients with elevated uric acid at the Genuk Community Health Center in Semarang. The study employed a descriptive analytical design with a cross-sectional approach, data collection through questionnaires, involving 66 respondents using total sampling technique, and statistical analysis using the Spearman Rho test. The results showed that the average age of respondents was 48 years old and they had been diagnosed with gout for 3 years, with the majority being male (60.6%), having a high school education (62.1%), working as private employees (48.5%), receiving high levels of family support (71.2%), and having good self-care behaviors (59.1%). The study concluded that there was a relationship between age and education with self-care in gout patients (p value < 0.05), but there was no relationship between gender and self-care (p value > 0.05).